FOOD INTAKE RATES AMONG INPATIENTS AT BHAYANGKARA HOSPITAL KENDARI 2025 - Indri Rambung; Febriana Muchtar; Syefira Salsabila (Media Inovasi Pendidikan dan Publikasi, 2026)
This study aims to determine the level of food acceptance among inpatients at Bhayangkara Hospital in Kendari. This is a quantitative observational study using a cross-sectional approach. The population consisted of 602 patients in classes I, I, and III. The sample comprised 86 patients selected using proportionate stratified random sampling. Data were collected through observation and interviews using a questionnaire, then analyzed using univariate analysis. The results showed that food acceptance based on appearance specifically food color was high for breakfast, lunch, and dinner. However, regarding portion size, acceptance tended to decrease, particularly for lunch and dinner, with most respondents stating that the portions were inadequate. Food acceptance levels based on taste decreased at lunch and dinner, with the majority of respondents stating that the food did not taste good. Regarding food aroma and texture, most respondents reported that they were appropriate at breakfast, lunch, and dinner. Meanwhile, regarding food temperature, most respondents reported that it was inappropriate at lunch and dinner. Overall, patient food acceptance was good in terms of color, aroma, and texture, but improvements are still needed regarding portion size, taste, and food temperature